Study on the Physiological and Biochemical Influence of Sargassum thunbergii Under Dehydration - Yanmin YUAN; Fuli LIU; Zhourui LIANG; Pengyan ZHANG; Yi LIU; Yanxin ZHENG; Haining ZHANG (Progress in Fishery Sciences, 2023)
Sargassum thunbergii is distributed on reefs and rock marshes in mid- and low-tide zones, and some are periodically exposed to lengthy low tides. Dehydration is a key factor affecting the survival of S. thunbergii at low tides. In this study, using wild S. thunbergii as experimental material, the water loss rate, chlorophyll fluorescence parameters, and biochemical parameters under different stresses were determined by dehydrating the thalli in an incubator for 0, 1, 3, and 6 h. The results showed that: (1) algae of different sizes have significantly different water loss rates under different stresses. The shorter the stress time and the larger the algae, the lower the water loss rate, indicating that the water retention capacity of S. thunbergii with larger thalli is higher. Wild S. thunbergii grow in clusters on reefs. The leaves in the lower part of the branches and near the holdfast are wide. The middle and upper leaves are narrow and long, respectively. The lower broad leaves are easily blocked by the upper branches. Therefore, differences in the growth environment cause differences in the ecological structure and biochemical components of S. thunbergii. High temperature, strong light, and water loss at low tide are the main factors that cause severe environmental stress to sessile S. thunbergii in the intertidal zone. (2) Dehydration significantly reduced the chlorophyll fluorescence value of S. thunbergii, and different parts of the same individual of S. thunbergii had significantly different tolerance to dehydration, with the lowest tolerance at branch tips and the strongest tolerance at the base. The non-regulatory energy-dissipation mechanism plays a major role in the dehydration response of S. thunbergii. Under dry exposure, the light energy utilization efficiency of S. thunbergii was significantly reduced. This reduction in active light protection capacity indicates that dehydration reduces the adaptability of S. thunbergii to excessive light intensity. Dehydration can damage the tips of small individuals that cannot recover, while the base part of large individuals could return to a normal physiological state. (3) Antioxidant enzymes (ASAFR, SOD) and non-antioxidant substances (soluble sugar and proline) in the tip part responded to dehydration, and the base part mainly responded by upregulation of protein, soluble sugar, and proline content to resist stress. S. thunbergii, located in the high and middle tide zones, is more likely to be stressed by high temperatures, strong light, and dehydration, and the physiological and biochemical characteristics of different parts of the thallus are also variable due to differences in external morphology. Algae mainly reduce damage to the photosynthetic system caused by a lack of water through a non-regulatory energy dissipation mechanism. The water retention capacity of the base was better than branch tips during dry exposure, and the damage to algal cells was low. The main roles are as heat shock proteins, soluble sugars, proline, and other small molecules, which can pass stress response, osmotic regulation, and anti-oxidation resists damage to cells caused by stress. The water retention capacity of the top cells was weak, and the stress was relatively strong. Antioxidant enzymes such as ASAFR and SOD in algae and non-antioxidant enzymes such as soluble sugars and proline, work together to resist dry exposure stress, reduce cell damage and maintain cell viability. In summary, under the stress of dry exposure, the antioxidant enzymes, antioxidant substances, and non-regulatory energy dissipation mechanisms of S. thunbergii play a role in maintaining cell activity. This study provides important guidance for exploring the ecological adaptability of S. thunbergii in resisting environmental stress.